Distinct transmission cycles of Leishmania tropica in 2 adjacent foci, Northern Israel - Svobodova, Milena; Votypka, Jan; Peckova, Jitka; Dvorak, Vít; Nasereddin, Abedelmajeed; Baneth, Gad; Sztern, Julia; Kravchenko, Vasiliy; Orr, Amnon; Meir, David; Schnur, Lionel F; Volf, Petr; et al. (Emerging infectious diseases, 2006)
Transmission of Leishmania tropica was studied in 2 adjacent foci in Israel where vector populations differ. Only Phlebotomus sergenti was found infected with L. tropica in the southern focus; P. arabicus was the main vector in the northern focus. Rock hyraxes (Procavia capensis) were incriminated as reservoir hosts in both foci. L. tropica strains from the northern focus isolated from sand flies, cutaneous leishmaniasis cases, and rock hyraxes were antigenically similar to L. major, and strains from the southern focus were typically L. tropica. Laboratory studies showed that P. arabicus is a competent vector of L. tropica, and P. sergenti is essentially refractory to L. tropica from the northern focus. Susceptibility of P. arabicus may be mediated by O glycoproteins on the luminal surface of its midgut. The 2 foci differ with respect to parasites and vectors, but increasing peridomestic rock hyrax populations are probably responsible for emergence of cutaneous leishmaniasis in both foci.
Keywords: leishmanióza kožní; mezerníky ribozomální DNA; Male; fluorescenční protilátková technika nepřímá; Polymerase Chain Reaction; polymerázová řetězová reakce; protozoální DNA; zdroje nemoci; Animals; Leishmania tropica; DNA, Protozoan; mužské pohlaví; Hyraxes; Female; damani; Disease Reservoirs; Fluorescent Antibody Technique, Indirect; ženské pohlaví; hmyz - vektory; DNA, Ribosomal Spacer; Leishmaniasis, Cutaneous; zvířata; Israel; Insect Vectors; Psychodidae; Izrael